Kinematic Properties of the Gaseous Stellar Dynamics Using the Tully-Fisher Relation in the Different Types of Spiral Galaxies - Al Najm, M. N (Iraqi Journal of Science, 2024)
The goal of this paper is to show the kinematic characteristics of gaseous stellar dynamics using scaling coefficient relationships (such as Tully-Fisher) in different spiral galaxies. We selected a sample of types of spiral morphology  (116 early, 150 intermediate, and 146 late) from previous literature work, and used statistical software (statistic-win-program) to find out the associations of multiple factors under investigation, such as the main kinematic properties of the gaseous-stellar (mass, luminosity, rotational speed, and baryons) in different types of spiral galaxies. We concluded that there is a robust positive connection between Log Vrot.max.) and Log Mstar(B-V), as well as between Log Vrot.max. and Log Mbar (B-V)  in  three types of spiral galaxies (early, intermediate, and late), with a sharply negative relationship found between  and Log MB in addition to the relationship between Log Mbar (B-V)  and Log MB, with the partial correlation coefficient (R ≈ - 0.85) in all the different types of spiral galaxies. Our results indicated that for early and intermediate kinds of spiral galaxies, the baryonic disk mass and the maximum rotational speed fit best with the formula Mbar (B-V) ≈ 60V4rot.max., but this relationship seems to be stronger in late-type spiral galaxies with Mbar (B-V) ~ 60 V5rot.max .  Whenever the observable stars and atomic hydrogen gas were taken into account, several scientific facts show that additional extremely massive baryon stores are virtually probably present in late spiral galaxies.